2013
DOI: 10.1371/journal.pone.0055758
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairments in Hashimoto’s Encephalopathy: A Case-Control Study

Abstract: Background/AimsHashimoto's encephalopathy is considered as a treatable dementia, but it is often misdiagnosed. We investigated cognitive impairment and the MRI pathology of Hashimoto's encephalopathy patients.MethodsThe study comprised eight patients with Hashimoto's encephalopathy, 16 patients with mild Alzheimer’s disease and 24 healthy subjects. A neuropsychological battery included assessments of memory, language, attention, executive function and visuospatial ability. Cranial MRI was obtained from all Has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
16
0
3
Order By: Relevance
“…The previous research demonstrated that cognitive impairment (84.6%) and psychiatric symptoms (38.5%) were the most frequent symptoms, however, seizures (30.8%) and myoclonus (7.7%) were relatively infrequent in thirteen consecutive patients with HE. [3] Therefore, presenting symptoms of HE may be quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…The previous research demonstrated that cognitive impairment (84.6%) and psychiatric symptoms (38.5%) were the most frequent symptoms, however, seizures (30.8%) and myoclonus (7.7%) were relatively infrequent in thirteen consecutive patients with HE. [3] Therefore, presenting symptoms of HE may be quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…AD is easily confounded by multi-infarct dementia and fronto-temporal dementia. Lewy body dementia [25], neuro-infections [26], depression [27], autoimmune encephalopathies [28] and normal pressure hydrocephalus [29] are easily misdiagnosed for AD. Not recognizing the treatable NCD forms may lead to missed treatment on one hand and unnecessary AD treatment on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Spontan remisyonlar bildirilmişse de nadirdir. [10] Ekstrapiramidal sistem bulgusu olarak daha sık tremor [4] bildirilmekle birlikte, yeni bildirilen bir olgu serisinde %7.7 ile tremor, nadir bulgulardan biridir. [11] Bizim hastamızdakine benzer tarzda parkinsonizm tablosunu taklit eden bir olgu sunumu bildirilmemiştir.…”
Section: Discussionunclassified
“…Hastalık progresif veya tekrarlayıcı bir seyir gösterebilir. [3][4][5] Klinik tablonun şiddeti tiroid fonksiyonlarından ziyade otoimmün antikor titresi ile ilişkilidir. Ancak otoimmün tiroid antikorlarının patogenezdeki yeri net olmamakla birlikte anti tiroid peroksidaz (anti-TPO) antikorlarının tiroid hücrelerine karşı hücresel toksisite ve komplemana bağlı hücresel toksisiteyi artırdığı bilinmektedir.…”
unclassified